1961
DOI: 10.1111/j.1365-2389.1961.tb00922.x
|View full text |Cite
|
Sign up to set email alerts
|

The Available‐water Capacity of a Sandy Loam Soil

Abstract: T o assess the effects of cultural and manurial treatments on the available-water capacity of a sandy loam soil it was necessary to determine the upper and lower limits of the available water.The results of determining the moisture content of the soil at field capacity (FC) by two methods have been compared. It has been found that the direct method involving soil sampling after irrigation and when drainage had almost ceased, gave more accurate and consistent results than the suction-plate method using any sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…As a result, -values from −33 to −5 kPa have been proposed to define FC (Richards and Weaver, 1944;Salter and Haworth, 1961;Linsley and Franzini, 1972;Romano and Santini, 2002;Kirkham, 2005;Nemes et al, 2011). More recently, Assouline and Or (2014) proposed a method to relate the slope of the soil characteristic curve (n), the air entry value ( ae ) and the residual water of a soil ( r ) (van Genuchten, 1980) to a soil specific FC, based on the balance between capillary and gravitational forces.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, -values from −33 to −5 kPa have been proposed to define FC (Richards and Weaver, 1944;Salter and Haworth, 1961;Linsley and Franzini, 1972;Romano and Santini, 2002;Kirkham, 2005;Nemes et al, 2011). More recently, Assouline and Or (2014) proposed a method to relate the slope of the soil characteristic curve (n), the air entry value ( ae ) and the residual water of a soil ( r ) (van Genuchten, 1980) to a soil specific FC, based on the balance between capillary and gravitational forces.…”
Section: Introductionmentioning
confidence: 99%
“…Field capacity, on the other hand, is sensitive to small changes in water potential and temperature, and its determination is the most difficult aspect of assessing the available water capacity of a soil (e.g. Salter and Haworth, 1961). Errors in determination of FC are of particular importance, since only water stored in a profile above a potential of about-1| atm.…”
Section: Smectoid Soil 20 24mentioning
confidence: 99%
“…The kaolinitic and montmorillonitic clay soils covering most of the Island have a rather massive structure and are frequently stony, and nothing was known about the constancy, or otherwise, of their 'field capacity'. We eventually abandoned approaches based on the pressure membrane apparatus, in-field determination of field capacity, and the other methods of assessing soil water attributes recently reviewed by Salter (1967), concentrating instead on large undisturbed soil monoliths removed from the field and stood side by side at the laboratory for comparison.To extract a monolith the two ends of a 44-gallon oil drum were removed and the resulting cylinder was placed upright on the soil at a carefully selected site. A pit was dug around the cylinder, leaving it standing on a central column of soil, which was trimmed as precisely as possible, with a machette, to the diameter of the drum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At Wellesbourne, a long-term experiment has shown that the supply of nutrients is only in part the reason for the very marked responses of vegetable crops there to FYM (Haworth, 1960). The soil at Wellesbourne contains 53% coarse sand, 28% fine sand, 10% silt, and 9% of clay (Salter & Haworth, 1961), and it compacts severely in dry weather. After 9 years, during which 20 tons of FYM per acre was applied to each crop and incorporated by rotavating (other methods of incorporation gave similar but smaller effects) the available water capacity (per unit of volume) in the top 6 in.…”
Section: Vol 24mentioning
confidence: 99%